Sodium hyaluronate/chitosan polyelectrolyte complex scaffolds for dental pulp regeneration: synthesis and characterization - Coimbra, Patrícia Manuela Almeida (2018)
In the present study, small-sized porous scaffolds were obtained from the freeze-drying of sodium hyaluronate/chitosan polyelectrolyte complexes. The obtained materials were characterized by a set of techniques including attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy, swelling determination and weight loss studies. The morphology of the scaffolds was observed using scanning electron microscopy. Thermal characterization ofthe scaffolds was also performed by dynamic mechanical thermal analysis and thermogravimetric analysis. Finally, the cytotoxic profile of the prepared scaffolds was evaluated in vitro, using mesenchymal stem cells. The results obtained showed that cells adhered to scaffolds and proliferated. This study also confirmed that the degradation by-products of sodium hyaluronate/chitosan scaffold are noncytotoxic, which is fundamental for its application in the biomedical field.